2023
DOI: 10.53365/nrfhh/158808
|View full text |Cite
|
Sign up to set email alerts
|

An <i>in silico</i> study involving Mangiferin, 7-Epiclusianone, Fukugetin, Lapachol, Plumbagin and Guttiferone-A against <i>C. albicans</i> proteins

Abstract: It is notorious that since the beginnings of spacetime, the human being lives with microorganisms of countless forms, be it in a positive way as in case of Bacteroidetes present in the intestine’s microbiota or negative way as in case of recent epidemic of Sars-Cov-2. So, the negative impacts caused by microorganisms are objects of study in the whole world, for instance, <i>Candida albicans</i>, which is a fungus that lives in the human body symbiotically and assists in the maintenance of body home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The binding activity of the receptor protein and the tiny ligand molecule FA are more stable when the binding energy is lower and more hydrogen bonds are present. Table 4 of the docking results revealed that FA's binding energy to the core target was less than or equal to 5 kcal/mol, indicating that the binding is meaningful (Barros et al, 2023;Gilson et al, 1997;Marcelino et al, 2022))and a docking is considered reliable if the RMSD of all ligand atoms is less than 2.0 Trott and Olson (2010).We selected the interaction of the binding conformation of hydrogen bond number ≥2 for visualization (Figure 5). The docking scores were recorded in Table 3.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…The binding activity of the receptor protein and the tiny ligand molecule FA are more stable when the binding energy is lower and more hydrogen bonds are present. Table 4 of the docking results revealed that FA's binding energy to the core target was less than or equal to 5 kcal/mol, indicating that the binding is meaningful (Barros et al, 2023;Gilson et al, 1997;Marcelino et al, 2022))and a docking is considered reliable if the RMSD of all ligand atoms is less than 2.0 Trott and Olson (2010).We selected the interaction of the binding conformation of hydrogen bond number ≥2 for visualization (Figure 5). The docking scores were recorded in Table 3.…”
Section: Molecular Docking Analysismentioning
confidence: 99%